2019
DOI: 10.3390/jcm8111854
|View full text |Cite
|
Sign up to set email alerts
|

Loop Diuretic Administration in Patients with Acute Heart Failure and Reduced Systolic Function: Effects of Different Intravenous Diuretic Doses and Diuretic Response Measurements

Abstract: Background: Despite the fact that loop diuretics are a landmark in acute heart failure (AHF) treatment, few trials exist that evaluate whether the duration and timing of their administration and drug amount affect outcome. In this study, we sought to evaluate different loop diuretic infusion doses in relation to outcome and to diuretic response (DR), which was serially measured during hospitalization. Methods: This is a post-hoc analysis of a DIUR-HF trial. We divided our sample on the basis of intravenous diu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Diuretics, including loop diuretics and tolvaptan, were often added when congestion remains after initial treatment. The increased use of loop diuretics was thought to have resulted in an increased frequency of WRF and longer length of hospital stay, as reported in a previous observational study 30 . Poor medical adherence is expected to avoid the tolvaptan use because we should monitor the serum sodium levels to avoid the rapid occurrence of hypernatraemia.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Diuretics, including loop diuretics and tolvaptan, were often added when congestion remains after initial treatment. The increased use of loop diuretics was thought to have resulted in an increased frequency of WRF and longer length of hospital stay, as reported in a previous observational study 30 . Poor medical adherence is expected to avoid the tolvaptan use because we should monitor the serum sodium levels to avoid the rapid occurrence of hypernatraemia.…”
Section: Discussionmentioning
confidence: 90%
“…After adjusting for confounders incorporating tolvaptan use as a time-updated covariate accounting for the time to start tolvaptan, the excess risk of tolvaptan use relative to no tolvaptan use was no longer significant for all-cause death, cardiovascular death, and non-cardiovascular death at 90 days of follow-up from the index hospitalization (adjusted HR = 1.53, 95% CI = 0.77-3.02, P = 0.22; adjusted HR = 2.00, 95% CI = 0.85-4.72, P = 0.11; adjusted HR = 0.82, 95% CI = 0.24-2.74, P = 0.74) (Table 3). Patients who used tolvaptan had a longer hospital stay [median 22 (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) days vs. 15 (11-21) days, P < 0.0001] and a higher prevalence of WRF (47.0% vs. 31.8%, P < 0.0001) and WHF (24.8% vs. 14.4%, P < 0.0001). Also, they more often had high-dose loop diuretic, dyspnoea on exertion, and oedema at discharge (Supporting Information, Table S1).…”
Section: Clinical Outcomes After 90 Days Of Follow-up From the Index ...mentioning
confidence: 99%
“…The authors reported As mentioned, multiple metrics have been proposed to evaluate the diuretic response, including weight loss in kilograms per unit of 40 mg of furosemide or equivalent. 7 An Italian study 14,15 included patients with acute HF and evaluated the effect of diuretic response (i.e. weight loss per 40 mg of furosemide) on the risk of death from cardiovascular cause and hospitalization due to HF during a 6-month follow-up.…”
Section: Therapeutic Advances In Cardiovascular Diseasementioning
confidence: 99%
“…In their study of 2,338 patients with HFrEF who were taking loop diuretics, ter Maaten et al found an increased independent risk of all-cause mortality and HF hospitalization with higher doses of loop diuretics [hazard ratio/doubling of loop diuretic dose: 1.06 (1.01-1.12), p=0.021] [ 30 ]. Ruocco et al observed that the outcome event rate (death due to cardiovascular causes or HF hospitalization) was significantly higher (75% vs. 22%, p<0.001) in patients with HF with reduced ejection fraction (<50%) in the high-dose intravenous furosemide group compared to those receiving a low dose [ 31 ]. Onitsuka et al reported that the use of high-dose furosemide (≥40 mg per day) was associated with an increased risk of cardiac events (cardiac death or re-hospitalization due to the worsening of HF) among HF patients with reduced ejection fraction (<45%) (adjusted HR=3.531, 95% CI=1.522-8.196, p=0.003) [ 32 ].…”
Section: Reviewmentioning
confidence: 99%
“…This is expected as aggressive diuresis will help promote fluid removal, reducing fluid overload symptoms in patients with HFrEF. On the other hand, Ruocco et al observed that diuretic response (daily weight loss per 40 mg of furosemide) at day three (0.106 (0.053-0.213) vs. 0.222 (0.127-0.407), p<0.001) and diuretic response during the entire infusion period (0.106 (0.064-0.240) vs. 0.266 (0.200-0.400), p<0.001) were lower in the high-dose intravenous loop diuretic group compared to the low-dose group, but no significant difference was observed at day one of admission [ 31 ]. They observed that patients who received high-dose intravenous loop diuretics had a significantly higher rate of congestion score >2 at the time of admission compared to the low-dose group (63% vs. 36%, p=0.003), so it is likely that this group of patients had more advanced disease and probably needed additional diuretic treatment that would stress the nephrons at a different site in order to achieve more efficient diuresis even with use of high-dose loop diuretics [ 31 ].…”
Section: Reviewmentioning
confidence: 99%